Contrasting changes in freshwater fish assemblages and food webs follow modification of tropical waterways. Issue 4 (28th June 2018) - Liew, Jia Huan; Giam, Xingli; Clews, Esther; Tan, Kenrick Y. W.; Tan, Heok Hui; Kho, Zi Yi; Yeo, Darren C. J.
Abstract: Fresh waters are increasingly threatened by flow modification. Knowledge about the impacts of flow modification is incomplete, especially in the tropics where ecological studies are only starting to emerge in recent years. Using presence/absence data dated approximately four decades apart ( 1966 to 2010) from 10 tropical rivers, we assessed the changes in freshwater fish assemblage and food web after flow modification. The sites were surveyed with methods best suited to habitat conditions (e.g., tray/push netting for low‐order forest streams, visual surveys for canalised rivers and net casting for impounded rivers). With the presence/absence data, we derived and compared six measures of fish assemblage and food web structure: species richness, proportion of native species, overall functional diversity, native functional diversity, food web complexity and maximum trophic level. We found that changes in community assemblage and food web structure were not generalisable across modification regimes. In canalised sites, species richness and maximum trophic levels were lower in the second time period while the opposite was true for impounded sites. However, proportion of native species was consistently lower in the second time period across modification regimes. Changes in fish assemblages and food webs appear to be driven by species turnover. We recorded 79 cases of site‐specific extirpation and 117 cases of site‐specific establishment. Our data further suggest that turnover in assemblage is again contingent on flow‐modification regime. While the process was stochastic in canalised rivers, benthopelagic species were more likely to be extirpated from impounded rivers where species lost were replaced by predominantly alien fish taxa.